Evaluation of the Semarang City Government's Social Media Performance in Increasing Public Engagement - Pujiastuti, Natalia Sari; Pramucitra, Sinta; Laksono, Agus Edy (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the implementation of principles and ethics in social media management based on PERMENPANRB No. 83 of 2012 on the Instagram accounts of Regional Apparatus Organizations (OPD) in the Semarang City Government. It also evaluates content strategies to enhance public engagement and build trust. This qualitative study observed 32 official Instagram accounts of OPD, utilizing content analysis, interviews, and engagement rate (ER) measurements with HypeAuditor tools. The results show that most OPD accounts have low ER, although some accounts achieved better performance through interactive and relevant content. Key challenges include limited human resources, lack of training for social media administrators, and a dominance of routine activity reporting without participatory communication strategies. Additionally, overlapping roles between content administrators and Public Information and Documentation Officers (PPID), coupled with a paternalistic leadership style within OPD, further contribute to the low level of public engagement. This study recommends optimizing social media management strategies through capacity building for account administrators, implementing two-way communication approaches based on data analytics, and establishing digital communication policies that promote flexibility and innovation. These strategies can enable government social media to function more effectively as a platform for transparency, interaction, and collaboration with the public, while sustainably building public trust.